The benefits of thermal clothing during winter in patients with heart failure: a pilot randomised controlled trial. Issue 4 (29th April 2013) - Barnett, Adrian G; Lucas, Margaret; Platts, David; Whiting, Elizabeth; Fraser, John F
Abstract : Objectives: To examine whether providing thermal clothing to heart failure patients improves their health during winter. Design: A randomised controlled trial with an intervention group and a usual care group. Setting: Heart failure clinic in a large tertiary referral hospital in Brisbane, Australia. Participants: Eligible participants were those with known systolic heart failure who were over 50  years of age and lived in Southeast Queensland. Participants were excluded if they lived in a residential aged care facility, had incontinence or were unable to give informed consent. Fifty-five participants were randomised and 50 completed. Interventions: Participants randomised to the intervention received two thermal hats and tops and a digital thermometer. Primary and secondary outcome measures: The primary outcome was the mean number of days in hospital. Secondary outcomes were the number of general practitioner (GP) visits and self-rated health. Results: The mean number of days in hospital per 100 winter days was 2.5 in the intervention group and 1.8 in the usual care group, with a mean difference of 0.7 (95% CI −1.5 to 5.4). The intervention group had 0.2 fewer GP visits on average (95% CI −0.8 to 0.3), and a higher self-rated health, mean improvement –0.3 (95% CI −0.9 to 0.3). The thermal tops were generally well used, but even in cold temperatures the hats were only worn by 30% of the participants. Conclusions: Thermal clothes are a cheap and simple intervention, but further work needs to be done on increasing compliance and confirming the health and economic benefits of providing thermals to at-risk groups. Trial registration: The study was registered with the Australian New Zealand Clinical Trials Registry (ACTRN12612000378820)